Exploring neutrino mixing with low energy superbeams - Minakata, Hisakazu [UNESP]; Nunokawa, Hiroshi (Springer Nature, 2001)
We explore the features of neutrino oscillation which are relevant for measurements of the leptonic CP violating phase δ and the sign of Delta;m13 2 in experiments with low-energy conventional superbeams. Toward the goal, we introduce a new powerful tool called the CP trajectory diagram in bi-probability space which allows us to represent pictorially the three effects, the effects of (a) genuine CP violation due to the sin δ term, (6) CP conserving cos δ term, and (c) fake CP violation due to earth matter, separately in a single diagram. By using the diagram, we observe that there is a two-fold ambiguity in the determination of S which is related with the sign of Delta;m13 2. Possible ways of resolving the ambiguity are discussed. In particular, we point out that an in situ simultaneous measurement of δ and the sign of Delta;m13 2 can be carried out at distances of about 700 km, or at the Phase II of the JHF experiment provided that sin δ ·Delta;m13 2 < 0, both with a megaton class water Cherenkov detector.
Keywords: Cp violation; Neutrino Physics; Solar and atmospheric neutrinos